Fast bilateral breast coverage with high spectral and spatial resolution (HiSS) MRI at 3T. Issue 5 (6th March 2017) - Medved, Milica; Li, Hui; Abe, Hiroyuki; Sheth, Deepa; Newstead, Gillian M.; Olopade, Olufunmilayo I.; Giger, Maryellen L.; Karczmar, Gregory S.
Abstract : Purpose: To develop and assess a full‐coverage, sensitivity encoding (SENSE)‐accelerated breast high spatial and spectral resolution (HiSS) magnetic resonance imaging (MRI) within clinically reasonable times as a potential nonenhanced MRI protocol for breast density measurement or breast cancer screening. Materials and Methods: Sixteen women with biopsy‐proven cancer or suspicious lesions, and 13 women who were healthy volunteers or were screened for breast cancer, received 3T breast MRI exams, including SENSE‐accelerated HiSS MRI, which was implemented as a submillimeter spatial resolution echo‐planar spectroscopic imaging (EPSI) sequence. In postprocessing, fat and water resonance peak height and integral images were generated from EPSI data. The postprocessing software was custom‐designed, and new algorithms were developed to enable processing of whole‐coverage axial HiSS datasets. Water peak height HiSS images were compared to pre‐ and postcontrast T 1 ‐weighted images. Fat suppression was quantified as parenchymal‐to‐suppressed‐fat signal ratio in HiSS water peak height and nonenhanced T 1 ‐weighted images, and artifact levels were scored. Results: Approximately a 4‐fold decrease in acquisition speed, with a concurrent 2.5‐fold decrease in voxel size, was achieved, with low artifact levels, and with spectral signal‐to‐noise ratio (SNR) of 45:1. Fat suppression was 1.9 times more effective ( P < 0.001) in HiSS images than in T 1 ‐weighted images (SPAIR), and HiSS images showed higher SNR in the axilla. HiSS MRI visualized 10 of 13 malignant lesions identified on dynamic contrast‐enhanced (DCE)‐MRI, and did not require skin removal in postprocessing to generate maximum intensity projection images. Conclusion: We demonstrate full‐coverage, SENSE‐accelerated breast HiSS MRI within clinically reasonable times, as a potential protocol for breast density measurement or breast cancer screening. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1341–1348.